"She just can't break it down to the classroom…": expert perspectives on German geography trainee teachers' competencies and initial teaching. Issue 3 (3rd July 2022) - Fischer, Frank
Abstract: Despite the preparatory service as a second practical phase of teacher training, German secondary geography teachers often experience a reality shock at the beginning of their teaching careers. Teacher trainers, the teacher educators of the second phase, guide trainee teachers through their transition from university to school. This qualitative study provides beneficial insights on geography trainee teachers' school practice from an expert point of view. Twenty-three teacher trainers from twelve different German states were interviewed. The data material was analysed with Mayring's qualitative content analysis. It was found that trainee teachers' preconditions vary massively, especially in terms of geography didactical knowledge (PCK). However, their average PCK preconditions seem to have improved over the last years. The teacher trainers perceive several subject-specific difficulties in the beginners' lessons, e.g. didactic reduction or applying geography didactical theory. Furthermore, the empirical data reveals the experts' perspectives on competencies of excellent geography trainee teachers. A need for a greater focus on actual teaching in initial teacher training as well as discrepancies between the different phases of geography teacher education are addressed at the end of the article.